Passive Solar and Conventional Housing Design: A Comparative Study of Daylighting Energy Efficiency Potential - Overen, Ochuko K.; Meyer, Edson L.; Makaka, Golden (Frontiers in Energy Research, 2021)
The increasing energy consumption and its resultant CO2 emission in the built environment have revolutionized the housing design. Buildings are strategically designed to harness ambient weather factors for indoor space thermal conditioning and lighting. A comparison of the daylighting and potential environmental mitigations due to the lighting energy consumption in a passive solar and the conventional house was the aim of this study. Both houses used as a case study are in Alice, Eastern Cape in South Africa. The indoor illuminance of the homes was monitored using Li-Cor 210R photometric sensors. Between 07 h00 to 16 h30, the passive solar house’s average daylighting was 217 lux and 56 lux in the conventional house on a clear sky. Under the same sky condition, there was 47% lighting energy saving. This reduces the amount of coal usage by 1.97 kg, 3.53 kg of CO2, 14.80 g of NO2, and 4.76 L of water. In contrast, no energy savings were achieved in the conventional home. The equivalent environmental impacts due to 4.20 kg of coal usage were 7.52 kg of CO2, 31.52 g of NO2 emissions, and 10.14 L of water usage. From the findings, daylight harvest through passive solar design shows the potential of energy savings and environmental mitigation measures in the housing sector.